Factor Associated with Adolescents Premarital Sexual Behavior at SMAN 1 Nagawutung, Nagawutung District Lembata Regency - Ina Abo, Maria Apolonia; Romeo, Petrus; Takaeb, Afrona E. L. (Lontar : Journal of Community Health, 2023)
The issue of sexuality, namely premarital sexual behavior, is one that frequently arises today. According to a survey by the Indonesian Family Planning Association and On Track Media Indonesia (OTMI), around 29%-31% of adolescents in East Nusa Tenggara had premarital sexual. The purpose of this study was to determine the factors associated with adolescent premarital sexual behavior at SMAN 1 Nagawutung District Lembata Regency. This type of research was an analytic observation with a cross-sectional design. The population was all students of classes XI and XII at SMAN 1 Nagawutung Lembata Regency, totaling 202 adolescents, and a sample of 66 adolescents was taken using proportional stratified random sampling. The statistical test used was the chi-square test. The results showed that exposure to information media (95% CI = 1,200 to 2,344; p-value = 0.015), parenting patterns (95% CI = 1,66 to 1,99; p-value = 0.042), and peers association (95% CI = 1,182 to 2,632; p-value = 0.008) had a relationship with adolescents premarital sexual behavior, while knowledge of reproductive health (95% CI = 0,701 to 4,357; p-value = 0.242) there is no relationship with adolescents premarital sexual behavior. To expand information about the effects of premarital sexual behavior, it is hoped that the school can collaborate with the Health Center. Adolescents need to build open communication with their parents, use media mass, commit themselves to refuse all shapes of sexual behavior, and be selective in choosing a partner.